Optimalisasi Agrowisata Melalui Tata Letak, Fasilitas, dan Strategi Promosi dalam Pengaruhnya pada Daya Saing Agrowisata Dukuhwringin Sejahtera Kabupaten Tegal - Muhamad Andi Budiyanto; Sari Wiyanti; Zahwa Saleh Seff (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research seeks to examine the impact of facilities., promotional strategies, and spatial layout on the competitiveness of agrotourism destinations. The research seeks to identify which factors play a dominant role in strengthening agrotourism competitiveness, both from the visitors’ perspective and the effectiveness of management practices. Employing a quantitative method through Partial Least Squares (PLS) analysis, data were collected through questionnaires distributed to visitors at the Dukuhwringin Sejahtera Agrotourism site in Tegal Regency.The findings reveal that the facilities variable has a positive and significant effect on agrotourism competitiveness, with a path coefficient of 0.222 and a significance value of (p = 0.036). This indicates that the better and more complete the facilities provided, the higher the level of comfort, attractiveness, and visitor satisfaction, which in turn enhances the destination’s competitiveness. Meanwhile, the promotional strategy (p = 0.214) and layout (p = 0.089) variables were found to have no significant effect on competitiveness. These results suggest that, although promotion and layout remain important, both have not yet been optimized to strengthen the competitive advantage of the agrotourism site.Overall, the study concludes that facilities are the dominant factor influencing the competitiveness of agrotourism destinations. Therefore, improving both physical and service-related facilities should be the main priority for agrotourism managers. Future studies are advised to incorporate additional variables like service quality, innovation, visitor satisfaction, and destination image to offer a more comprehensive insight into the factors influencing agrotourism competitiveness in Indonesia